Association between social determinants of health and premature atherosclerotic cardiovascular disease and sex differences in US adults: A cross-sectional study - Chun Yang; Na Zhang; Tiankuo Gao; Yingxin Zhu; Chen Gong; Mingyue Xu; Cuicui Feng (Preventive Medicine Reports)
Background: Premature atherosclerotic cardiovascular disease (ASCVD) is a major public health issue, leading to productivity losses and higher healthcare costs. This study examines the association between social determinants of health (SDoH) and premature ASCVD, with a focus on sex differences. Method: Data on self-reported SDoH based on Healthy People 2030 criteria were obtained from U.S. National Health and Nutrition Examination Surveys (2003–2018). Weighted logistic regression models were used to examine the relationship between SDoH (including eight sub-items and the cumulative number of unfavorable SDoH) and premature ASCVD. Analyses were further stratified by sex. Result: A total of 40,536 participants aged ≥18 years (19,548 men and 20,888 women) were included in the analysis. The overall prevalence of premature ASCVD was 1756 cases, with a weighted estimate of 7,625,240. Although women had a lower prevalence of premature ASCVD (3.2 % [n = 784] vs. 4.3 % [n = 972]), they exhibited a higher level of unfavorable SDoH compared to men. Logistic regression indicated a 21 % increase in risk for each additional unfavorable SDoH (AOR = 1.21; 95 % CI, 1.16–1.26), and the cumulative number of unfavorable SDoH were positively associated with the odds of developing premature ASCVD (P for trend <0.01). Notably, the impact of unfavorable SDoH was greater in women, revealing significant sex disparities in susceptibility to premature ASCVD. Conclusion: This study demonstrates that unfavorable SDoH significantly increase the risk of developing premature ASCVD. Furthermore, the cumulative effect of unfavorable SDoH pose a higher risk for women.